Effect of multivitamin and multimineral supplements on morbidity from infections in older people (MAVIS trial): pragmatic, randomised, double blind, placebo controlled trial. Issue 7512 (4th August 2005) - Avenell, Alison; Campbell, Marion K; Cook, Jonathan A; Hannaford, Philip C; Kilonzo, Mary M; McNeill, Geraldine; Milne, Anne C; Ramsay, Craig R; Seymour, D Gwyn; Stephen, Audrey I; Vale, Luke D
Abstract: Objective To examine whether supplementation with multivitamins and multiminerals influences self reported days of infection, use of health services, and quality of life in people aged 65 or over. Design Randomised, placebo controlled trial, with blinding of participants, outcome assessors, and investigators. Setting Communities associated with six general practices in Grampian, Scotland. Participants 910 men and women aged 65 or over who did not take vitamins or minerals. Interventions Daily multivitamin and multimineral supplementation or placebo for one year. Main outcome measures Primary outcomes were contacts with primary care for infections, self reported days of infection, and quality of life. Secondary outcomes included antibiotic prescriptions, hospital admissions, adverse events, and compliance. Results Supplementation did not significantly affect contacts with primary care and days of infection per person (incidence rate ratio 0.96, 95% confidence interval 0.78 to 1.19 and 1.07, 0.90 to 1.27). Quality of life was not affected by supplementation. No statistically significant findings were found for secondary outcomes or subgroups. Conclusion Routine multivitamin and multimineral supplementation of older people living at home does not affect self reported infection related morbidity. Trial registration ISRCTN: 66376460.